Comprehensive Physiology 2013
DOI: 10.1002/cphy.c120018
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Nervous System and Neurobiology of the Liver

Abstract: The liver has a nervous system containing both afferent and efferent neurons that are involved in a number of processes. The afferent arm includes the sensation of lipids, glucose, and metabolites (after eating and drinking) and triggers the nervous system to make appropriate physiological changes. The efferent arm is essential for metabolic regulation, modulation of fibrosis and biliary function and the control of a number of other processes. Experimental models have helped us to establish how: (i) the liver … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
148
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(151 citation statements)
references
References 101 publications
(165 reference statements)
2
148
0
1
Order By: Relevance
“…Similarly, within hepatic parenchyma such an increase of innervation may impair blood supply within the sinusoidal area and also could have an impact on hepatocyte metabolism; the activity of Kupffer cells and hepatic stellate cells [20]. Sympathetic regulation within the parenchyma of hepatic lobules is not only involved with the regulation of liver physiology, but it could also be related with several pathophysiological processes such as liver repair and regeneration [21].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, within hepatic parenchyma such an increase of innervation may impair blood supply within the sinusoidal area and also could have an impact on hepatocyte metabolism; the activity of Kupffer cells and hepatic stellate cells [20]. Sympathetic regulation within the parenchyma of hepatic lobules is not only involved with the regulation of liver physiology, but it could also be related with several pathophysiological processes such as liver repair and regeneration [21].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it has been shown that GLP-1 activates phosphoinositide 3-kinase/PKB in rat hepatocytes and stimulates the activity of glycogen synthase a (23). Alternatively, the effect of GLP-1 on the liver could be mediated by binding to the GLP-1 and glucose receptors on nerve terminals in hepatic hilum area (as well as in the fibers extending into the connective tissue and hepatic lobules and ending on liver parenchymal cells in humans) (14). This in turn would initiate a neural signal to the brain and from the brain via efferent fibers to other organs (adipose tissue, muscle, liver itself) involved in a coordinated response to a glucose challenge.…”
Section: E649mentioning
confidence: 95%
“…These signals (glucose, GLP-1, gastric inhibitory polypeptide, PYY, etc.) are sensed by several areas: gut and afferent nerves and vasculature, wall of the portal vein, liver, and other organs in the general circulation (14). It is possible that the putative effects of exenatide or GLP-1 mediated by portal sensors were mitigated by compensatory changes such that portal denervation by comparison had a minimal impact on the overall response to a glycemic load and oral glucose tolerance.…”
Section: E649mentioning
confidence: 99%
“…The liver is affected by both the sympathetic and the parasympathetic nerve systems. These nerve systems modulate information regarding hepatic osmolality, glucose concentrations, and lipid concentrations from the brain through the afferent neurons, and the liver receives varieties of signals including blood flow, bile secretion, and metabolism through the efferent neurons [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%